The Development of Collaborative Learning Cell Based on Brain-Based Learning (BBL)Model for The Junior High School Science Learning in The Agroecosystem Area - Ari Dwi Setya Laksana; Jekti Prihatin; Ika Lia Novenda (BIOEDUKASI, 2019)
Agroecosystem plays an important role in the national economy. However, the role of agroecosystem in education in the form of teaching and learning has not been used optimally. It is less in providing opportunities for students to develop their mindset based on their abilities so that the students do not understand the potential requiring the surrounding area. Learning models that can provide opportunities for students to develop are suitable with the 2013 curriculum. Modification of collaborative learning Cells with Brain-Based Learning (BBL LC) model makes the learning appropriate for the 2013 curriculum. The purpose is to obtain a valid, effective, and practical model which is suitable for the junior high school science learning in the agroecosystem area. The research type is development research (R & D) by using the 4-D model but, only use three stages; Define, Design, and Develop stages without using Disseminate stage. This research was conducted at Junior High School 7 Jember. The data collection techniques were filling out the validation sheet, interview, observation, test, and documentation. The data analysis techniques include data analysis from the validation results, model analysis, and model effectiveness analysis. The model validity was the average results of the product validation (85.81%) in a very valid category. The model effectiveness was the average of¬N-gain learning outcomes (0.53) and students' problem-solving skill questionnaires (75.87% ) in a good category. The model practicality was from the teacher and student response questionnaires with an average of about 92.94% and 94% which belongs to a very practical category.